Melhora dos marcadores sanguíneos inflamatórios em pacientes com hipotireoidismo em tratamento com levotiroxina - Marchiori, Roseane Cardoso (2015)
Introduction: Some studies suggest that patients with hypothyroidism have systemic inflammation and increased oxidative stress and consider these factors may contribute to the increased risk of atherosclerosis and atherosclerotic cardiovascular disease in these patients. Few studies have evaluated the effect of treatment of hypothyroidism on inflammatory markers and oxidative stress, with conflicting results. Background: The aim of this study was to investigate the effect of levothyroxine replacement therapy on biomarkers of oxidative stress and systemic inflammation in patients with hypothyroidism. Methods: Patients with recently diagnosed primary hypothyroidism due to Hashimoto´s thyroiditis who were not taking levothyroxine were included. The following blood parameters were measured at pre-treatment, at six and twelve months of levothyroxine: thyroid stimulating hormone (TSH), free thyroxine (FT4), high sensitive C-reactive protein (hs-CRP), interleukin-1 (IL-1), interleukin-6 (IL-6), interleukin-10 (IL-10), interferon gamma (INF-γ), tumor necrosis factor alpha (TNF-α), thiobarbituric acid reactive substances (TBARS), activity of the aminolevulinic acid dehydratase enzyme (δ-ALA-D), nonprotein and total thiol (NP-SH and T-SH) groups, total cholesterol (TC), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C) and triglycerides (TG). Generalized estimating equation (GEE) modeling was used to analyze the effect of treatment (at baseline, six and twelve month of follow-up) on the variables mentioned above. The hypothyroidism status (overt or subclinical hypothyroidism) was included as a confounder in all analyses. An additional GEE post hoc analysis was made with intent to compare time by time. Results: There was a significant decrease in TSH levels over time (P<0.0001) (initial levels were on average 32.4 μIU/mL and 10.5 μIU/mL at 12 months). There was a significant increase in FT4 (P<0.0001) over treatment (initial levels were on average 0,8 ng/dL and 2.7 ng/dL at 12 months). There were significant changes in interleukin levels over time, with significant increase in IL-10 (P<0.0001) and significant decrease of IL-1 (P<0.0001), IL-6 (P<0.0001), INF-γ (P<0.0001) and TNF-α (P<0.0001). No significant difference in hs-CRP levels over time was found (P<0.284). There was a significant reduction of NP-SH levels (P<0.0001) during follow-up. Conclusions: This study observed reduction of oxidative stress biomarker, reduction of pro-inflammatory cytokines and increase of anti-inflammatory cytokine in hypothyroid patients treated with levothyroxine. These modifications may have clinical relevance because the hypothesis that inflammation and oxidative stress may contribute to the development of atherosclerosis and cardiovascular disease in these patients.